2007
DOI: 10.1590/s0034-72992007000200016
|View full text |Cite
|
Sign up to set email alerts
|

Intensidade de ruído em hospital de 222 leitos na 18ª Regional de Saúde - PR

Abstract: Envi ronment noise pollution is common place today, at intolerable levels. In hospitals, technological developments have, as a consequence, potentially harmful noise levels. Much of the hospital noise comes from inside, rather than outside, and the major source of such noise is the Intensive Care Unit, for example equipment and hospital staff talk. Our goal with the present study was to investigate the noise level present in the different hospital environments, within a 222 bed hospital located at the 18th hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
3
22
0
8
Order By: Relevance
“…Although there was no significant oscillation during the observation, those changes may be clinically important to the evaluated population because ofthe gestational immaturity of the infants combined with the associated stressing agents and the increased susceptibility to the environmental stimuli which they are exposed to 2,4,7,14,18,19 .…”
Section: Discussionmentioning
confidence: 94%
“…Although there was no significant oscillation during the observation, those changes may be clinically important to the evaluated population because ofthe gestational immaturity of the infants combined with the associated stressing agents and the increased susceptibility to the environmental stimuli which they are exposed to 2,4,7,14,18,19 .…”
Section: Discussionmentioning
confidence: 94%
“…According to the National Committee of Noise and Auditive Preservation 19 , one of the symptoms of hearing loss induced by noise, is the beginning and the predominance 4 in the frequencies of 3, 4 or 6kHz, particularly in the first 10 to 15 years of exposure and, as the lesion worsens, it afterwards Besides, in other studies, the TEOAE and the DPOAE tests proved being more sensitive regarding the identification of cochlear alteration than the tonal liminal audiometry, having the TEOAE revealed greater sensitivity to cochlear changes 5 and the DPOAE allowed the diagnosis of eventual lesion in higher levels, even in individuals with quantitatively normal hearing regarding the tonal audiometry 10,12,13,23 .…”
Section: Discussionmentioning
confidence: 95%
“…Numberless studies have indicated the extreme noise in several hospital environments, and pointed out the need for prevention, as well as, for proper guidance for the professionals, particularly regarding those involved with the area of health, where, theoretically, the awareness for silence should be of major importance [2][3][4][5][6][7] .…”
Section: Source Of Support: Fundação De Amparo à Pesquisa Do Estado Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Em estudo realizado para verificar os níveis de ruído em um setor de esterilização, constatou que estes níveis estavam elevados, pois a média foi de 66 decibéis (18) , sendo que os níveis aceitáveis de ruídos são de 34 a 45 decibéis (19) . Embora não tenham sido verificados os níveis de decibéis a que os trabalhadores do presente estudo estiveram expostos, infere-se que seja necessário o uso destes EPIs, entretanto, no presente estudo nenhum trabalhador os utilizou.…”
Section: Discussionunclassified